2009
DOI: 10.1519/jsc.0b013e31818f058b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Caloric Restriction and Overnight Fasting on Cycling Endurance Performance

Abstract: In addition to aerobic endurance and anaerobic capacity, high power-to-weight ratio (PWR) is important for cycling performance. Cyclists often try to lose weight before race season to improve body composition and optimize PWR. Research has demonstrated body fat-reducing benefits of exercise after fasting overnight. We hypothesized that fasted-state exercise in calorie-restricted trained cyclists would not result in performance decrements and that their PWR would improve significantly. We also hypothesized that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 26 publications
4
16
0
2
Order By: Relevance
“…Therefore, if a longer period of intermittent fasting were to be carried out, it is likely that the performance would recover. This notion is in line with the study by Ferguson et al (2009), which showed that, after three weeks of fasting, aerobic performance was not affected due to an improvement in the power to weight ratio at 90-100% of VO2max [20]. Meanwhile, post-exercise plasma glucose was elevated in both groups to replenish the amount utilised during the high intensity exercise which relies mainly on endogenous carbohydrate stores as a fuel source can produce an increase in plasma glucose within a few minutes.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, if a longer period of intermittent fasting were to be carried out, it is likely that the performance would recover. This notion is in line with the study by Ferguson et al (2009), which showed that, after three weeks of fasting, aerobic performance was not affected due to an improvement in the power to weight ratio at 90-100% of VO2max [20]. Meanwhile, post-exercise plasma glucose was elevated in both groups to replenish the amount utilised during the high intensity exercise which relies mainly on endogenous carbohydrate stores as a fuel source can produce an increase in plasma glucose within a few minutes.…”
Section: Discussionsupporting
confidence: 87%
“…Based on the data in the current literature and as reviewed by Waterhouse [2] , Chaouachi et al [3] , Moughan [4] , and Mujika et al [5] , the effects of Ramadan intermittent fasting on metabolism, body mass and performance have been the subject of several studies performed over the last three decades, but the findings have been relatively inconsistent. In this context, although previous studies have failed to observe substantial performance decrements following shorter periods of fasting (11−24 h) [6,7] , other investigators concluded that fasting before exercise causes a decrement in performance [8,9,10] . Most of these studies used sedentary or recreationally active individuals who were undertaking exercise tasks at which they were relatively inexperienced.…”
Section: Introductionmentioning
confidence: 99%
“…There are reports of cyclists trying to enhance their power-to-weight ratio at the expense of energy intake. 29 Furthermore, due to prolonged exercise, cyclists may be at risk of having suboptimal energy intake during training, which has been associated with low bone mass. 1 30 Unfortunately, eating habits and the prevalence of RED-S are unknown in our sample.…”
Section: Discussionmentioning
confidence: 99%